2004
DOI: 10.1111/j.1365-2249.2004.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic enzymes associated with the cell surface of Streptococcus pneumoniae are antigenic in humans and elicit protective immune responses in the mouse

Abstract: SUMMARYStreptococcus pneumoniae is a leading cause of otitis media, sinusitis, pneumonia, bacteraemia and meningitis worldwide. The drawbacks associated with the limited number of various capsular polysaccharides that can be included in the polysaccharide-based vaccines focuses much attention on pneumococcal proteins as vaccine candidates. We extracted an enriched cell wall fraction from S. pneumoniae WU2. Approximately 150 soluble proteins could be identified by 2D gel electrophoresis. The proteins were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 44 publications
8
156
0
3
Order By: Relevance
“…Those studies also observed GAPDH and other common antigens found in L. garvieae stains (Shin et al, 2007(Shin et al, , 2009. Moreover, despite studies citing GAPDH as a promising vaccine to protect against Edwardsiella tarda, Vibrio anguillarum and S. pneumonia (Ling et al, 2004;Liu et al, 2005Liu et al, , 2007, efficacy of the GAPDH vaccine from L. garvieae has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies also observed GAPDH and other common antigens found in L. garvieae stains (Shin et al, 2007(Shin et al, , 2009. Moreover, despite studies citing GAPDH as a promising vaccine to protect against Edwardsiella tarda, Vibrio anguillarum and S. pneumonia (Ling et al, 2004;Liu et al, 2005Liu et al, , 2007, efficacy of the GAPDH vaccine from L. garvieae has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH is a potential vaccine for protecting against Edwardsiella tarda and Streptococcus pneumonia (Ling et al, 2004;Liu et al, 2005). Protective in several ways, GAPDH may protect antigenicity against other pathogenic bacteria in fish .…”
Section: Discussionmentioning
confidence: 99%
“…GAS α-enolase shares 49% identity with human α-enolase), which raises concern for autoimmune consequences [24]. For further characterization we chose three candidates that are not represented in the human proteome and do not share significant amino acid sequence identity with other human proteins as determined by BLAST-P interrogation (Supplementary Table 1): arginine deiminase (ADI) [25,26] and trigger factor (TF) [27,28], which are potential GAS virulence determinants, and fructose bisphosphate aldolase (FBA), which affords vaccine protection against Streptococcus pneumoniae [29]. All three enzymes lack N-terminal signal sequences and C-terminal cell wall anchors [7].…”
Section: Proteomic Analysis Of Gas Cell Wall Extractsmentioning
confidence: 99%
“…GAPDH, as well as a number of other cytoplasmic proteins, has been found on the surface of S. mutans and other streptococci (Henderson & Martin, 2011;Ling et al, 2004;Severin et al, 2007). An investigation by Biswas & Biswas (2005) found that deletion of the HtrA extracellular protease/chaperone resulted in increased levels of extracellular GAPDH in culture media.…”
Section: Extracellular Gapdh Activity Is Increased In Yidc Mutantsmentioning
confidence: 99%